2000
DOI: 10.1111/j.1752-0606.2000.tb00300.x
|View full text |Cite
|
Sign up to set email alerts
|

Biracial Youth and Families in Therapy: Issues and Interventions

Abstract: Empirical research and clinical resources focusing specifically on minority youth and families have increased tremendously in the last 2 decades. Despite this trend, certain groups continue to be relatively neglected. In particular, very few resources exist for understanding the unique challenges that often face biracial youth and their families. In this article, we use a nationally representative database to compare functioning in biracial youth to white adolescents and other minority adolescents. Results sug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
109
2

Year Published

2006
2006
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(119 citation statements)
references
References 9 publications
6
109
2
Order By: Relevance
“…Additionally, using mental health as a latent variable for anxiety and depression, multiracial adolescents were found to have more mental health issues than monoracial Caucasians and African Americans. This is consistent with other investigations that have found higher levels of depression in multiracial adolescents than in adolescents from other ethnic groups (Cooney & Radina, 2000;Milan & Keiley, 2000).…”
Section: Mental Health Differencessupporting
confidence: 82%
See 1 more Smart Citation
“…Additionally, using mental health as a latent variable for anxiety and depression, multiracial adolescents were found to have more mental health issues than monoracial Caucasians and African Americans. This is consistent with other investigations that have found higher levels of depression in multiracial adolescents than in adolescents from other ethnic groups (Cooney & Radina, 2000;Milan & Keiley, 2000).…”
Section: Mental Health Differencessupporting
confidence: 82%
“…Researchers speculate, and some findings support, that the complex nature of identity development for multiracial youth will contribute to weaker identity development and thus more issues with psychological adjustment (Brown, 1990;Coleman & Carter, 2007;Lusk, Taylor, Nanney, & Austin, 2010;Milan & Keiley, 2000;Park, 1928;Stonequist, 1961;Teicher, 1968;Udry, Li, & Hendrickson-Smith, 2003;Williams & Thornton, 1998). Others oppose the notion that multiple identities may lead to poor psychological outcomes, stating that one cannot assume that having two or more identities would lead to difficulties in identity development (Kato, 2000).…”
Section: Ethnic Identity and Mental Health Outcomesmentioning
confidence: 99%
“…Effect sizes (partial eta squared), however, were so small, varying between .001 and .003, that these statistical findings did not represent meaningful differences. Therefore, the current study found evidence of fewer difficulties of multiracial young adults relative to their monoracial peers, when compared to previous researchers who studied the same sample as adolescents and found consistent patterns of negative well-being (Milan & Keiley, 2000;Udry et al, 2003). In part this may be because previous researchers did not present effect sizes.…”
contrasting
confidence: 51%
“…Udry, Li and Hendrickson-Smith (2003) studied 3,539 multiracial adolescents ages 12 to 18 and found they had increased psychological adjustment, health and behavior risks when compared to monoracial adolescents. The researchers used data from the National Longitudinal Study of Adolescent Health (Add Health; Bearman, Jones, & Udry, 1997), a nationally representative school-based probability sample of 90,118 children in grades 7 through 12 conducted initially in 1994. Milan and Keiley (2000 found similar results, also using the same Add Health data.…”
mentioning
confidence: 59%
See 1 more Smart Citation